2019
DOI: 10.1093/sysbio/syz002
|View full text |Cite
|
Sign up to set email alerts
|

Priors and Posteriors in Bayesian Timing of Divergence Analyses: The Age of Butterflies Revisited

Abstract: The need for robust estimates of times of divergence is essential for downstream analyses, yet assessing this robustness is still rare. We generated a time-calibrated genus-level phylogeny of butterflies (Papilionoidea), including 994 taxa, up to 10 gene fragments and an unprecedented set of 12 fossils and 10 host-plant node calibration points. We compared marginal priors and posterior distributions to assess the relative importance of the former on the latter. This approach revealed a strong influence of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
162
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 123 publications
(174 citation statements)
references
References 58 publications
12
162
0
Order By: Relevance
“…Two hesperiid fossils, Pamphilites abdita Scudder and Protocoeliades kristenseni de Jong, were candidates to be included as fossil calibrations for this study (de Jong, ). However, preliminary testing in beast revealed that the age estimates obtained with these two fossils were largely underestimated compared with the ages from Espeland et al () or Chazot et al (). This discrepancy is partly due to the difficulty of placing the oldest described skipper fossil into an extant taxon: Protocoeliades kristenseni from Denmark, dated at c .…”
Section: Methodsmentioning
confidence: 70%
See 2 more Smart Citations
“…Two hesperiid fossils, Pamphilites abdita Scudder and Protocoeliades kristenseni de Jong, were candidates to be included as fossil calibrations for this study (de Jong, ). However, preliminary testing in beast revealed that the age estimates obtained with these two fossils were largely underestimated compared with the ages from Espeland et al () or Chazot et al (). This discrepancy is partly due to the difficulty of placing the oldest described skipper fossil into an extant taxon: Protocoeliades kristenseni from Denmark, dated at c .…”
Section: Methodsmentioning
confidence: 70%
“…76 Ma and the split between Hesperiidae and Hedylidae to be c . 106 Ma, and Chazot et al () estimated these nodes to c . 65 Ma and c .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies estimated the age of Coliadinae at c . 42 and 48 Ma (in Espeland et al ., and Chazot et al ., , respectively). We took two secondary calibration points from the latter which covered most Coliadinae genera.…”
Section: Methodsmentioning
confidence: 88%
“…We followed a conservative approach by using uniform priors encompassing the 95% highest posterior density (HPD) intervals from Chazot et al . (). The constrained nodes included the divergences of: (i) Brassolini and Morphini to 32–58 Ma; (ii) Melaniti and Dirini to 23–47 Ma; (iii) Lethina, Parargina and Mycalesina to 25–44 Ma; (iv) the crown age of Satyrini to 32–53 Ma; (v) the crown age of the Satyrini's subclade encompassing the tribes Pronophilina, Euptychiina, Satyrina, Erebiina, and other closely related subtribes, to 25–43 Ma; and (vi) the crown age of Satyrinae to 41–67 Ma.…”
Section: Methodsmentioning
confidence: 97%